Literal and metaphorical usages of "˜eat' and "˜drink' verbs in Nzema communication - NYAME, JOHN (Informasi, 2025)
Eating and drinking form part of the daily activities of the Nzema. This paper investigates metaphorical extensions associated with the consumption verbs di "˜to eat' and no "˜to drink' in Nzema (Kwa, Bia). It seeks to explore domains in which the verbs are utilised metaphorically to relay everyday concepts and cognitive processes in the Nzema language. Data for the study comprise conversations collected from four respondents. The paper first presents a brief discussion on the components that comprise the central meanings of the verbs. The verbs and their metaphorical extensions are discussed under two major themes: Agent-oriented extensions and patient-oriented extensions. Under agent-oriented extensions, figurative usages that are based on the internalization of food as well as extensions based on the sensation of the agent undergoing the event are discussed. Extensions derived from the destruction of food during the process of consumption is discussed under the patient-oriented. The paper finds that in Nzema, the verb di "˜to eat' is utilised metaphorically to convey ideas such as to arbitrate, seduce, take oath, misappropriate among others. The verb no "˜to drink' conveys ideas such as to inhale or smoke, and to sponge. Remarkably, some metaphorical extensions of consumption verbs that are not reported in other African languages, such as extensions of eat for squabbling, for taking oath, for insinuating, for witnessing and for hunting, and the extensions of drink for sponging are present in Nzema.